The Effects of Rosmarinic Acid on Hippocampal Oxidative Stress Markers in LPS-induced Neuroinflammation Rats: Rosmarinic Acid and Hippocampal Oxidative Stress - Ahmadi-Zohan, Atiyeh; Hassanzadeh-Taheri, Mohammadmehdi; Hosseini, Mehran (Iranian Journal of Pharmaceutical Sciences, 2021)
Neuroinflammation (NI) plays a pivotal role in the pathogenesis of several neurodegenerative diseases. It has been believed that alleviating NI can be a valuable approach in controlling the progress of neurodegenerative diseases. The generation of reactive oxygen and nitrogen species could trigger and deteriorate NI. According to previous studies, rosmarinic acid (RA) could exhibit neuroprotective potential. Therefore, this study aimed to evaluate the effect of RA on hippocampal oxidative stress markers in lipopolysaccharide (LPS)-induced NI in rat brain. A total of 24 adult male Wistar rats were randomly allocated into four equal groups (n=6 each) and NI was induced in three of them by intracerebroventricular (ICV) injection of LPS (50 μg/20μl; 10 μl into each ventricle). RA (2.5-5 mg/kg i.p.) was injected 30 min before the LPS injection and continued once per day up to 48 h. On day 3, animals were sacrificed and their hippocampi were dissected. Then, hippocampal concentrations of malondialdehyde (MDA), superoxide dismutase (SOD), and nitric oxide (NOx) were determined. RA prevented hippocampal MDA elevation in a dose-dependent-manner and increased SOD activity but did not affect NOx content. In conclusion, the results of the present study demonstrated that systemic administration of RA could effectively ameliorate oxidative stress induced by LPS in rat’s brain. This potential might be one of the underlying mechanisms through which RA mitigates NI.